Two-step enzymatic strategy for the synthesis of a smart phenolic polymer and further immobilization of a β-galactosidase able to catalyze transglycosydation reaction - Levin, Gustavo Javier (2018)
A rapid and efficient enzymatic procedure for the preparation of an immobilized β-galactosidase has been described. In a first step, soybean peroxidase was used to catalyze the polymerization of a strategically activated phenol (N–Succinimidyl 3–(4–hydroxyphenyl)propionate, known as Bolton-Hunter reagent). The phenolic support was directly employed for immobilizing β–galactosidase from Bacillus circulans (ATCC 31382, β–Gal–3), giving rise to a new biocatalyst subsequently applied in the synthesis of a β–galatodisaccharide (Gal–β(1–3)–GlcNAc and Gal–β(1–3)–GalNAc). The reaction proceeded with high conversion rates and total regioselectivity. Reusability assays were performed with the same reaction conditions finding that the immobilized enzyme retains about 55% of its activity after eight batches. Finally and based on our results, the two-step enzymatic procedure presented here is a good and green alternative to the preparation of carbohydrates with biological activities.